The Role of Using Motorized Diamond Burr Polisher Instrument in Minimizing the Recurrent Rate of Pterygium Excision - Nidhamalddin, Sakar Abdulkarim (Kurdistan Journal of Applied Research, 2020)
To compare the effects of using motorized diamond burr polisher in pterygium excision versus manual polishing of the corneoscleral bed in reducing the recurrent rate. A prospective, comparative and interventional study of 90 consecutive patients with different grads of primary pterygium, who underwent pterygium excision at Shahid Aso teaching eye hospital in Sulaimani city, between August 2018 till September 2019, which was performed by single surgeon. In group A (45) eyes polishing of the corneoscleral bed done using motorized diamond polishing burr, and in group B (45) eyes using manual crescent blade for polishing. Recurrent rate was evaluated after about (8±2) months postoperatively. Ethical consideration of the risks and the benefits of the procedure was observed for each individual patient. A 90 patients with the mean age of group A (48.84±12.7) years and group B (49.67±12.3) years, complained of different grads of primary pterygium, group A had 31(68.9%) male and 14(31.1%) female, while group B had 22(48.9%) male and 23(51.1%) female. Each individual factors like age, gender, visual acuity, BCVA pre and postoperatively, IOP measurement, dryness of the eye and risk factors like smoking and UV exposure affecting the recurrence were assessed. In both groups the main indication for surgery was sign of irritation. The mean surgical time was calculated and the difference between two groups were significant. After follow-up of average six months the outcomes and recurrent rate were checked, recurrent rate was in group A 1(2.2%) while in group B was 6(13.3%) patients. it significantly decreased. Corneal scar happens in only 1(2.2%) case of group A while in 11(24.4%) cases in group B, Corneal scar was statistically significant. In both groups the change of BCVA was significant but the visual change was more significant in group A in compare to group B. Motorized diamond burr is a safe instrument for polishing the cornea during pterygium excision, it is easy to handle, low price, need lesser operative time, its effect on recurrence postoperatively is significant and beside it leaves lesser corneal scar and early visual recovery postoperatively.